56‐1: Enhancing Response Time of Quantum‐Dot‐Based TFT Photosensor with Self‐Assembled Monolayer. Issue 1 (28th June 2021) - Jeon, Gilsu; Seo, Taewon; Ko, Hyungmin; Park, Hyuk; Kwon, Jisu; Ha, Taeyong; Kim, Sungjee; Chung, Yoonyoung
Abstract : Quantum‐dot‐based a‐IGZO phototransistor has become one of the promising devices for image sensor application due to its bandgap tunability and solution‐process compatibility. However, the QD phototransistor with a‐IGZO, which contains a large amount of charge traps on the surface, exhibited slow photoresponse (τdecay >10 s). In this work, the photocurrent and decay time were significantly enhanced by 2.2 times and 73%, respectively, by introducing a self‐assembled monolayer (SAM), which effectively passivates the traps at the QD/a‐IGZO interface.